Design of an adsorbent employing activated carbon fiber to remove lead - Cárdenas-López, C.; Camargo, Gabriel; Giraldo, Liliana; Moreno-Piraján, Juan Carlos (Eclética Química, 2007)
Zorflex® activated carbon fibers (ACF), reference FM100 198B, are used before and after an oxidizing procedure with H 3 PO 4 to study the adsorption of Pb 2+ . The point of zero charge was determined for the modified and unmodified fiber giving values of 2.3 and 4.3, respectively. After oxidizing the ACF, the fiber showed to have a greater Pb 2+ adsorption capacity in comparison with the unmodified fiber, which is related with the acid sites increase, where lead was mainly adsorbed. Determination of the BET area was carried out by nitrogen physisorption at 77K. ACFs presented superficial areas between 1000 and 1500 m 2 /g showing mostly, a microporous structure. The preliminary design of an adsorbent using the modified fiber is presented where the fiber superior physicochemical properties over the unmodified one are observed.